The Effect of Balance Training on Increasing the Accuracy of Ushiro Mawashi Geri Kicks in Karate - Aly Rachmat; Sagittarius; Ivan Rivan Firdaus; Mulyana (Universitas Negeri Semarang, 2025)
The purpose of this study was to determine whether there was an effect of balance training on increasing the accuracy of the ushiro mawashi geri kick in committee athletes in the karate sport. This study was conducted in an all-experimental method. The subjects of the study were 10 from the Student Activity Unit karate upi athletes. The instrument used was the accuracy of the ushiro mawashi geri kick. Data analysis techniques used ( Descriptive static, test of normality and paired sample T-test). Based on the results of the descriptive static analysis, the minimum pretest and posttest values were 5, the maximum value was 10, the average pretest value of 10 athletes was 6.70 and the standard deviation was 1,636. In the posttest there was a minimum value of 7, a maximum value of 10, the average posttest value of 10 athletes was 8.80 and the standard deviation was 1.398. For normality results If the data is normally distributed or the significance value is > 0.05 then the next step is to use the paired sample t-test , the normal pretest kick accuracy is 0.003 and the normal significance value in the posttest is 0.004. The paired sample T-test data given shows a difference in pairs (Pair Differences) of -2.600 and 1.506 with a mean (average) of 0.476, the 95% confidence interval for the difference is -5.461 to 9. The test shows a significant increase with the results (2-tailed) 0.000 (p <0.05). that it can be concluded that balance training can affect the improvement of the accuracy of the ushiro mawashi geri kick.